Digital Textbooks - Sadiku, Matthew N. O.; Sadiku, Janet O.; Chukwu, Uwakwe C. (International Journal on Integrated Education, 2023)
Digital textbooks are the future of education, making learning more affordable and accessible for all. A digital textbook is essentially an electronic rendition of a traditional print textbook with more features. It is accessed through a computer or smartphone and can be read online or downloaded for offline reading. It helps students to learn better and improve their overall learning experience. It is an easy, convenient, and thoroughly modern way of accessing academic information. Digital textbooks are causing radical changes in education, affecting the ways teachers teach and student learn. This paper provides an introduction on digital textbooks, identifying their pros and cons.